Role of Lipopolysaccharide Sialylation in Serum Resistance of Serogroup B and C Meningococcal Disease Isolates - Vogel, Ulrich (American Society for Microbiology, 1999)
α-2,3-Sialyltransferase mutants of three genetically and phenotypically diverse Neisseria meningitidis strains were compared with regard to resistance to human serum and systemic spread in the infant rat. Lipopolysaccharide sialylation was found to be of minor importance for the resistance of serogroup B and C meningococcal disease isolates to complement attack.